2013
DOI: 10.1002/jsfa.6432
|View full text |Cite
|
Sign up to set email alerts
|

Berry antioxidants: small fruits providing large benefits

Abstract: Small berry fruits are consumed because of their attractive colour and special taste, and are considered one of the richest sources of natural antioxidants. Their consumption has been linked to the prevention of some chronic and degenerative diseases. The term 'berry fruits' encompasses the so-called 'soft fruits', primarily strawberry, currants, gooseberry, blackberry, raspberry, blueberry and cranberry. The objective of this review is to highlight the nutraceutical value of berries and to summarize the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(205 citation statements)
references
References 115 publications
(215 reference statements)
2
189
1
13
Order By: Relevance
“…Those products are essential for a balanced healthy died and are highly requested by consumers [14]. Berry species are more and more requested for their richness in vitamins, minerals, amino acids, active principles, especially anti oxidants [15], being considered functional food [16]. "Super Fruits" as blackberry, raspberry, blueberry [17], black and red currant [12], sea buckthorn (Hippophae rhamnoides), chokeberry (Aronia melanocarpa), honeysuckle (Lonicera caerulea), wolfberry/Go Ji (Lycium barbarum) are produced in temperate zones for fresh consumption and processing, their cultivation being possible with high efficiency in small family farms and urban areas [6].…”
Section: Family Fruit Farms Potentialmentioning
confidence: 99%
“…Those products are essential for a balanced healthy died and are highly requested by consumers [14]. Berry species are more and more requested for their richness in vitamins, minerals, amino acids, active principles, especially anti oxidants [15], being considered functional food [16]. "Super Fruits" as blackberry, raspberry, blueberry [17], black and red currant [12], sea buckthorn (Hippophae rhamnoides), chokeberry (Aronia melanocarpa), honeysuckle (Lonicera caerulea), wolfberry/Go Ji (Lycium barbarum) are produced in temperate zones for fresh consumption and processing, their cultivation being possible with high efficiency in small family farms and urban areas [6].…”
Section: Family Fruit Farms Potentialmentioning
confidence: 99%
“…It is consumed either fresh or in such prepared foods as fruit juice, pies, ice creams, milkshakes, and chocolates 27 . Earlier reports have shown that strawberry consumption has the capacity to decrease cardiovascular disease risk and its phytochemicals possess anti-infl ammatory or anticancer properties 27-29 .…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds represent a large group of secondary metabolites [102], among them flavonoids, phenolic acids, tannins and tocopherols as the most common natural source phenolic antioxidants [103].…”
Section: Nonenzymatic Antioxidant Systemsmentioning
confidence: 99%
“…The phenolic compounds are composed of one or more aromatic rings with varying degrees of hydroxylation, methoxylation and glycosylation, and various studies have associated the structure of phenolic compounds with their antioxidant properties [102,104]. The antioxidant activity generally increases with the degree of hydroxylation in aromatic rings and decreases with C-3 methoxylation [105,106].…”
Section: Nonenzymatic Antioxidant Systemsmentioning
confidence: 99%